Value creation with big data analytics for enterprises: a survey - Ali Mirarab; Seyedeh Leili Mirtaheri; Seyed Amir Asghari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The emergence of Big Data applications has paved the way for enterprises to use Big Data as a value-creation strategy for their business; however, the majority of enterprises fail to know how to generate value from their massive volumes of data. Big Data Analytics results can help the enterprises in better decision-making and provide them with additional profits. Studying different researches dedicated to value creation through Big Data Analytics. This paper (a) highlights the current state of the art proposed for creating value from Big Data Analytics, (b) identifies the essential factors and discusses their effects upon value creation, and (c) provides a classification of the cutting-edge technologies in this field.